2000
DOI: 10.1034/j.1399-6576.2000.440615.x
|View full text |Cite
|
Sign up to set email alerts
|

Total versus tube‐related additional work of breathing in ventilator‐dependent patients

Abstract: In tracheally intubated or tracheostomized spontaneously breathing patients, adequate compensation of tube resistance (i.e. with minimal overcompensation and minimal undercompensation) is best done by the ATC mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 10 publications
0
26
0
2
Order By: Relevance
“…Wird dieses Verfahren ein-bis zweimal täglich angewendet, so sollte Unterkompensation infolge Sekretablagerung wirkungsvoll verhindert werden können. [26]. Obwohl die zusätzliche, durch den Tubuswiderstand bedingte Atemarbeit auch mit einer geeignet hohen (konstanten) Druckunterstützung im Modus PSV wirkungsvoll vermindert werden kann, geht diese Art der Tubuskompensation unweigerlich mit einer Über-druckbeatmung (infolge der unvermeidbaren Überkompensation des Tubuswiderstandes), und dementsprechend immer auch mit einer partiellen Beatmung des Patienten einher [13,26].…”
Section: Partielle Tubusobstruktionunclassified
“…Wird dieses Verfahren ein-bis zweimal täglich angewendet, so sollte Unterkompensation infolge Sekretablagerung wirkungsvoll verhindert werden können. [26]. Obwohl die zusätzliche, durch den Tubuswiderstand bedingte Atemarbeit auch mit einer geeignet hohen (konstanten) Druckunterstützung im Modus PSV wirkungsvoll vermindert werden kann, geht diese Art der Tubuskompensation unweigerlich mit einer Über-druckbeatmung (infolge der unvermeidbaren Überkompensation des Tubuswiderstandes), und dementsprechend immer auch mit einer partiellen Beatmung des Patienten einher [13,26].…”
Section: Partielle Tubusobstruktionunclassified
“…Banner, et al (1994) The literature supported the fact that there is an increase in WOBi with airways but results of the studies showed considerable differences. Straus et al (1998) found the WOB of the ETT to be approximately 11% while Haberthur et al (2000) measured the tube related WOB at approximately 52%. Straus et al used the acoustic reflection method to measure resistance of the ETT and supraglottic airway (1998) while Keidan et al (2000) and Haberthur et al (2000) used traditional flowmeters, esophageal balloons, and tracheal measurements to obtain their data.…”
Section: Introductionmentioning
confidence: 99%
“…Straus et al (1998) found the WOB of the ETT to be approximately 11% while Haberthur et al (2000) measured the tube related WOB at approximately 52%. Straus et al used the acoustic reflection method to measure resistance of the ETT and supraglottic airway (1998) while Keidan et al (2000) and Haberthur et al (2000) used traditional flowmeters, esophageal balloons, and tracheal measurements to obtain their data. All of the studies used small sample sizes and the populations varied from pediatric patients to adults.…”
Section: Introductionmentioning
confidence: 99%
“…17 In ATC mode, a ventilator measures flow and calculates the pressure required to overcome the flow-dependent resistive work load of the ETT. [5][6][7][8][9] The ATC calculations/algorithms are assuming a new, clean, and not deformed tube; because the calculation is based on the inner diameter and length of the ETT as well as on the measured flow, changes in the inner diameter of the ETT can hamper the accuracy of this calculation. Decrease in inner diameter induces increase in resistance, thus pressure drop is underestimated, and compensation is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…4 Automatic tube compensation (ATC) was developed to overcome the ETT-imposed respiratory work load. [5][6][7][8][9] ATC is designed to increase airway pressure by continuously calculating the pressure drop across the ETT (⌬P ETT ) during inspiration. [5][6][7][8][9] Theoretically, it simulates spontaneous breathing without the ETT, and appears to be suitable for use during the weaning period.…”
Section: Introductionmentioning
confidence: 99%